Design and Optimization of a Self-Nanoemulsifying Drug Delivery System for Pranlukast Hemihydrate with D-Optimal Mixture Design: D-Optimal Design based SNEDDS development for Pranlukast Hemihydrate - Jagadish, Kaveri Raja; Paravastu, Venkata Kamala Kumari; Saranya, Palavalasa (Iranian Journal of Pharmaceutical Sciences, 2025)
The researchers optimized the concentrations of components in the SNEDDS formulation using a D-optimal mixture design, aiming to achieve favorable physicochemical characteristics like dissolution and droplet size. The optimized formulation of pranlukast-loaded SNEDDS, comprising 22.44 mg of Benzyl alcohol, 67.55 mg of Tween 20, and 10 mg of Span 20, resulted in a droplet size of 65.866 nm, saturated solubility of 20.56 mg/g, and drug release of 90.84%, with a desirability index value of 1. The comparison of among experimental and predicted values for the droplet size, saturated solubility, and the drug release showed good agreement. Consequently, they successfully developed an SNEDDS formulation using a D-optimal mixture design, which is promising for enhancing weakly water-soluble drugs’ oral absorption.